Improved reading of the Koran at TPQ Nurul Iman Sukaharja Village - Yusuf, Maulana; Nurzaelani, Mohammad Muhyidin (Jurnal Pengabdian Nusantara, 2023)
TPQ Nurul Iman experienced several obstacles in teaching and learning activities to read and write the Koran, this caused a problem that prevented a goal from being achieved so it was necessary, for community service activities in the PPM scheme to be carried out to increase reading the Koran at TPQ Nurul Iman. The purpose of PPM activities is to increase the ability and understanding of TPQ teachers in the implementation of learning using the tilawati method. Help increase the understanding of tajwid material and its practice for TPQ Nurul Iman students. As well as improving and developing the abilities of TPQ Nurul Iman teachers in delivering Al-Qur'an reading learning materials that are not boring and easy to understand. The results of the PPM activities are to provide additional insight and knowledge and skills to the teaching staff at TPQ Nurul Iman. Growing passion and enthusiasm for student learning to improve the ability to read the Koran by conveying various recitation materials and practicing little by little the science of tajwid and still according to the tilawati method. As well as helping TPQ Nurul Iman to obtain facilities to support learning activities to read the Koran.